Hunting notes from Outernet: The embodiment of images after the Internet - Fresneda, Javier (Re-visiones, 2024)
This paper describes the infiltration of the image from the Internet to the everyday environment, what is beginning to be called the Outernet. However, this shift toward the physical space – architectural, urban, geological – is performed by prioritizing the technical and informative character of the image, which reduces the body to stationary and dissociated situations. From this point of departure we propose a parallel situation, in which we present the body as a transducer between image-providing devices and environments. We will consider the Outernet from its rereading as a low-fidelity Wilderness, a hybrid landscape where the body can hunt and embody image in a wild way – not entirely rational –, here described as performative research. Shifting the intentionality of our movements, we unfold a field of relationships in which the image is distributed along the body, the device, and the environment.